2006
DOI: 10.1038/sj.cr.7310113
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of plant microRNA gene families

Abstract: MicroRNAs (miRNAs) are important post-transcriptional regulators of their target genes in plants and animals. miRNAs are usually 20-24 nucleotides long. Despite their unusually small sizes, the evolutionary history of miRNA gene families seems to be similar to their protein-coding counterparts. In contrast to the small but abundant miRNA families in the animal genomes, plants have fewer but larger miRNA gene families. Members of plant miRNA gene families are often highly similar, suggesting recent expansion vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
93
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(112 citation statements)
references
References 47 publications
16
93
1
2
Order By: Relevance
“…In contrast, animal MIRNA genes in a cluster usually are not homologs although they are evolutionarily related, such as those in the miR-17 gene cluster. These non-homologous MIRNA genes could regulate multiple functionally related genes simultaneously [38].…”
Section: Highly Conserved Mir156b/c Among Cerealsmentioning
confidence: 99%
“…In contrast, animal MIRNA genes in a cluster usually are not homologs although they are evolutionarily related, such as those in the miR-17 gene cluster. These non-homologous MIRNA genes could regulate multiple functionally related genes simultaneously [38].…”
Section: Highly Conserved Mir156b/c Among Cerealsmentioning
confidence: 99%
“…In contrast to most animal miRNAs, plant miRNAs are usually transcribed from large gene families consisting of multiple miRNA precursors (Li and Mao, 2007). Similar to protein-coding gene families, miRNA gene families, including the miR164 genes, probably originated from gene or genome duplications, and subsequently underwent functional diversification to acquire specific biological functions (Maher et al, 2006).…”
Section: Coordinate Control Of Multiple Mirnasmentioning
confidence: 99%
“…For those miRNAs with multiple coding genes, the multiple coding genes were regarded as a miRNA gene family. For most arthropod species, the miRNA gene families are much smaller than those of plant species (Li et al, 2007;Nozawa et al, 2010). The miRNA origin for Arthropods is quite different from plants.…”
Section: Literature Review Mirnasmentioning
confidence: 99%
“…Previous miRNA studies indicated that miRNA families with larger size usually have relatively low abundance in plant species while those with smaller family size have higher abundance in animal species (Li et al, 2007). The largest miRNA family identified previously is the miRNA family miR395 in rice, which contains 24 perfectly matched coding genes (GUDDETI, 2005).…”
Section: Expansion Of Hessian Fly Mirna Familiesmentioning
confidence: 99%